Internalisasi Makna Simbolik Nilai Etnopedagogi "Gembyangan Waranggana Tayub" pada Pembelajaran IPS Untuk Penguatan Kompetensi Sikap: Internalisasi Makna Simbolik Nilai Etnopedagogi "Gembyangan Waranggana Tayub" pada Pembelajaran IPS Untuk Penguatan Kompetensi Sikap - Ratnaningtyas, Ratih (Jurnal Dialektika Pendidikan IPS, 2022)
Gembyangan Waranggana Tayub is an important procession to continue the Nyadran tradition in Sambirejo Village which is synonymous with Waranggana and Tayub. Internalization of the symbolic meaning of ethnopedagogical values ??from the Gembyangan Waranggana Tayub procession in learning as an effort to inculcate and pass on cultural values ??to students. The purpose of this research is to identify the symbolic meaning of the ethnopedagogical values ??of the Gembyangan Waranggana Tayub tradition and describe the achievement of internalizing the ethnopedagogical values ??of Gembyangan Waranggana Tayub towards strengthening the religious and social attitudes of students at SMPN 3 Tanjunganom, Nganjuk district. This study uses descriptive qualitative methods with data collection techniques through observation, interviews and documentation. The results of the study indicate that the value of ethnopedagogy can be interpreted through the symbols in the Gembyangan Waranggana Tayub procession. The procession of the Gembyangan Waranggana Tayub, namely; Kirab-an Waranggana, sprinkling holy water, drinking holy water, tearing hibiscus leaves, installing Cunduk Pentul, Pronunciation of Pledge, Ubengan around Mbah Ageng's well by dancing and singing 10 obligatory gendhing, then the Langen Tayub performance. The values ??contained include religious values, social values, self-confidence values, cooperative values, responsibility values, and mutual cooperation values. Internalization of values ??through social studies learning is achieved to strengthen the competence of religious and social attitudes of students at SMPN 3 Tanjunganom. The achievement of value internalization was obtained from the results of the observation sheet assessment and Value Clarification Technique (VCT) assessment at three meetings which showed complete attitudes in the "Very Good" and "Good" categories. The achievement of internalization is supported by the integration of local culture with the school curriculum.